Cross-cultural validation of stool Based Colorectal cancer screening methods in the North West of Iran. (April 2022) - Dolatkhah, Roya; Somi, Mohammad Hossein; Dastgiri, Saeed; Asghari Jafarabadi, Mohammad; Mashhadi Abdolahi, Hossein; Shanehbandi, Dariush; Asadi, Milad; Nezamdoust, Marzieh; Dolatkhah, Neda; Farassati, Faris
Abstract: Background: Globally, colorectal cancer (CRC) is the third most common cancer and the second leading cause of death from cancer. Incidence and mortality from CRCboth can be reduced and prevented using screening and early detection programs. The current study aimed to assess the feasibility of the colorectal cancer screening program in Northwest of Iran. Methods: The study designed as a cross-cultural analytic study, to evaluate the diagnostic accuracy of stool-based tests compared with colonoscopy, during 2016–2020. All individuals first were assessed with our CRC risk assessment tool, then eligible volunteers entered the study. Colonoscopy was performed on all participants, also stool-based tests including traditional guaiac, high-sensitivity guaiac-based, fecal immunochemical test (FIT), and multitarget stool DNA (Mt-sDNA) panel tests were performed. Results: Mt-sDNA test panel had a sensitivity of 77.8% (95% CI: 40–97.2)for detecting colorectal cancer with a specificity of 91.2% (95% CI:85.4–95.2). The FIT test alone had a lower sensitivity (66.7%; 95% CI:29.9–92.5) and almost the same specificity of 93.9% (95% CI: 88.7–97.2) for cancer detection. Mt-sDNA test had better diagnostic accuracy than the FIT (AUC = 0.85 vs 0.80), and is a more useful screening test. Positive and negative predictive values for cancer detection for both Mt-sDNA and FIT tests were almost the same results, however Mt-sDNA test had better NPV results than the FIT test alone. Conclusion: Our results showed that both Mt-sDNA panel and the FIT test had acceptable cut-off points for cancer detection, however, Mt-sDNA test had better diagnostic accuracy. Highlights: A priority of Iranian health policy must be to develop an executive plan to identify the appropriate CRC screening method. This study provides a first step toward the design of a population-based CRC screening program in East Azerbaijan, Iran. The current study has been performed to evaluate the diagnostic accuracy of stool-based tests for CRC screening. Our results showed that both Mt-sDNA panel and the FIT test had acceptable cut-off points for cancer detection. Among four stool -based tests, Mt-sDNA test had the highest sensitivity for detection of cancer and advanced adenoma.